ABOUT THE MISS IN TRANSLATED NOVELL “ГОСПОЃИЦА”: (ON MACEDONIAN LANGUAGE VERSUS MISS IN NOVEL “ГОСПОЂИЦА” (ON SERBIAN LANGUAGE) (Philological Studies, 2019)
With this symbolic title we want to point out the scientific and research analysis of the Macedonian translation of the novel "Mademoiselle" by Ivo Andric. Within the former Yugoslav state, Ivo Andric was one of the Yugoslav writers, who was also translated into Macedonian. This novel was published as book 3. and in "Collected Works by Ivo Andric" (directed by Muharrem Pervic, Petar Dzadzic). The edition of 1977, edition of "Misla", Skopje, will be taken. The translation is by Ilija Korubin. Our research is centered around the translation and adaptation of the noun "miss" from Serbian to Macedonian language.